The Researcher’s Role: An Ethical Dimension - Postholm, May Britt; Madsen, Janne (Outlines. Critical Practice Studies, 2006)
Different paradigms or perspectives function as the point of departure and framework for research. In this article ethical issues in the positivist and constructivist paradigms are presented. The article points out that more or less the same ethical codes are used in these paradigms, but with some nuanced interpretations. CHAT (cultural historical activity theory) is presented as a third paradigm. While conducting research, one intention within this paradigm is to change and improve practice. This means that the researcher and the research participants during the research process together set the goals for the work and try to change practice en route to these goals. The relation between the researcher and the research participants is different than in the other two presented paradigms. This means that research in the CHAT paradigm also needs to be guided by different ethical codes. The purpose of this article is to show how some of the traditional ethical codes which direct research both in the positivist and constructivist paradigm change and are also inadequate in the CHAT paradigm. The article presents and discusses ethical codes that challenge the researchers’ communicative, social and knowledge competence.